AVERAGE CALCULATIONS FOR ASSESSMENT EXAM TYPING ELECTRICALLY DISTRIBUTION METHOD USING FREQUENCY - Jamilah Jamilah; Susi Wagiyati, SKom, MMSI Susi Wagiyati, SKom, MMSI (Jurnal Sistem Informasi, 2002)
Frequency distribution is the preparation of a data starting from the smallest to thelargest number that divides the data into several classes. Usefulness of incoming datain the frequency distribution is to facilitate the presentation of data, easily understoodand easy to read as information material, in turn dihgunakan for calculating theaverage of a class and give an evaluation.The problem in perhitunan average is the number of data must be sorted before beingprocessed it will be increasingly difficult if the calculations are done manually. Tosimplify and accelerate the process of calculating the average writer tries to takeadvantage of advances in computer technology to create application programs for thecalculation of the average electric typing test assessment using Turbo Pascalprogramming.